Design studies of the magnetic properties of structural materials affecting the magnetic field of high-homogeneity superconducting magnets - Baldan, C. A. [UNESP]; Shigue, C. Y.; Ruppert-Filho, E.; Ortiz, W. A. (Elsevier, 2001)
Austenitic stainless steel presents phase changes caused by heat treatment and welding processes. Because it represents a problem in the design of high-homogeneity magnets, we have been studying the magnetic properties of Ti alloys for their use instead of stainless steel as structural material for superconducting magnet construction. In this work, we present the comparative study of the influence of magnetic properties of steel and Ti alloys on the magnetic-field homogeneity of a superconducting coil through numerical calculation using the measured magnetic properties. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Alloys; Austenitic steel; Magnetization; Superconducting magnets; Austenitic; Comparative studies; Design studies; Numerical calculation; Phase Change; Structural materials; Super-conducting coils; Ti alloys; Welding process; Austenite; Austenitic stainless steel; Cerium alloys; Electromagnets; Magnetic fields; Magnetic properties; Materials properties; Nanocrystalline alloys; Superconducting materials; Superconductivity; Titanium alloys